PERFORMANCE IMPROVEMENT OF CORE GMPLS NETWORKS USING 2-D CODE LABEL AND OPTICAL HARD-LIMITERS - Ngoc, Dang The; Ban, Nguyen Tien (Vietnam Journal of Science and Technology, 2012)
The standard core GMPLS networks consist of two layers, Fiber Switch Capable (FSC) and Wavelength Switch Capable (LSC). To extend the core switch capacity, code switch capable (CSC) layer has been added. The CSC layer, however, induces the complexity of the networks. In this paper, we propose a novel scheme of two-dimensional (2-D) optical code label for core GMPLS networks. In our proposal, the LSC layer and CSC layer are combined into one, i.e., 2-D CSC layer. The complexity of the GMPLS networks is therefore reduced while the core switch capacity is still enhanced. In addition, to the mitigate multiple-access interference (MAI), we propose to use optical hard-limiters (OHLs) at the core switches. Numerical results show that the throughput is increased significantly and able to reach the peak value.